Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1093/annonc/mdj059
|View full text |Cite
|
Sign up to set email alerts
|

Dalteparin for prevention of catheter-related complications in cancer patients with central venous catheters: final results of a double-blind, placebo-controlled phase III trial

Abstract: Dalteparin prophylaxis did not reduce the frequency of thromboembolic complications after CVC implantation in cancer patients. Dalteparin was demonstrated to be safe over 16 weeks of treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(136 citation statements)
references
References 28 publications
3
131
0
2
Order By: Relevance
“…144 For prevention of CVAD-associated VTE, randomized controlled studies have not established the efficacy of prophylactic doses of LMWH or lowdose warfarin (1 mg daily). [145][146][147] A recent randomized trial showed that dose-adjusted warfarin (INR, 1.5-2.0; n=473) was significantly more effective than fixed-dose warfarin (1 mg daily; n=471) in preventing CVAD-associated VTE at a cost of a trend toward more bleeding; however, a separate comparison of warfarin (fixed 1-mg dose, n=324; adjusteddose, INR1.5-2, n=84) with placebo (n=404) did not demonstrate a statistically significant reduction in VTE. 148 These data suggest therapeutic or neartherapeutic doses of anticoagulation will likely be necessary for the successful prevention of CVADassociated VTE.…”
Section: Vte Prophylaxismentioning
confidence: 99%
“…144 For prevention of CVAD-associated VTE, randomized controlled studies have not established the efficacy of prophylactic doses of LMWH or lowdose warfarin (1 mg daily). [145][146][147] A recent randomized trial showed that dose-adjusted warfarin (INR, 1.5-2.0; n=473) was significantly more effective than fixed-dose warfarin (1 mg daily; n=471) in preventing CVAD-associated VTE at a cost of a trend toward more bleeding; however, a separate comparison of warfarin (fixed 1-mg dose, n=324; adjusteddose, INR1.5-2, n=84) with placebo (n=404) did not demonstrate a statistically significant reduction in VTE. 148 These data suggest therapeutic or neartherapeutic doses of anticoagulation will likely be necessary for the successful prevention of CVADassociated VTE.…”
Section: Vte Prophylaxismentioning
confidence: 99%
“…[85][86][87] The choice to start prophylaxis against venous thromboembolic events in all oncology patients bearing a CVC, either with LMWH or with minidose warfarin, remains unsupported by evidence-based medicine. However, more studies are needed to identify subsets of cancer patients who are at high risk of developing CVC thrombosis and may benefit from prophylactic systemic anticoagulation.…”
Section: Thrombosismentioning
confidence: 99%
“…The outpatient prophylaxis score developed by Khorana et al 4 (Table iii) and validated in randomized trials identifies cancer patients at risk for vte. Anticoagulants tested in cancer patients include dalteparin, enoxaparin, tinzaparin, semuloparin, certoparin, bemiparin, nadroparin, and warfarin [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , of which enoxaparin, dalteparin, and tinzaparin are readily available in Canada. A Cochrane systematic review 43 of 21 rcts that included 9861 ambulatory patients with cancer receiving chemotherapy showed that, compared with inactive control and warfarin, low molecular weight heparin (lmwh) was associated with a 45% reduction in the overall vte incidence [risk ratio: 0.55; 95% confidence interval (ci): 0.34 to 0.88; p < 0.05] and a nonsignificant increase in bleeding.…”
Section: Prophylaxis In Ambulatory Cancer Patientsmentioning
confidence: 99%